Effect of MDR1 C3435T and CYP2C19 genetic polymorphisms on the outcome of Helicobacter pylori eradication treatment in children with gastritis and peptic ulcer, Vietnam - Loan Le Thi Thuy; Liem Thanh Nguyen; Hoang Anh Vu; Nghia An Nguyen; Tuan Anh Nguyen (BMC, 2024)
Abstract Background Helicobacter pylori eradication therapy based on antimicrobial susceptibility in Vietnamese children currently get low efficiency. There are causes of treatment failure, among host genetic factors namely MDR1 C3435T and CYP2C19 affect the absorption and metabolism of proton pump inhibitors - a crucial component of eradication therapy. The study aimed to investigate the effect of MDR1 C3435T and CYP2C19 genetic polymorphisms on the cure rate. Methods 207 pediatric patients with gastritis and peptic ulcer infecting Helicobacter pylori completed the eradication therapy based on antimicrobial susceptibility with proton pump inhibitor esomeprazole. Eradication efficacy was assessed after at least 4 weeks by the urease breath test. MDR1 C3435T genetic polymorphism and CYP2C19 genotype were determined using a sequencing method based on Sanger's principle. Results Among 207 children recruited in this study, the ratio of CYP2C19 EM, IM, and PM phenotypes was 40.1%, 46.4%, and 16.9%, respectively. The patient with MDR1 3435 C/C polymorphism accounted for 43.0%, MDR1 3435 C/T was 40.1%, and MDR1 3435T/T was 16.9%. The cure rate of Helicobacter pylori infection in patients with CYP2C19 EM genotype was 78.3%; 83.3% of those with the IM genotype, and PM genotype was 96,4% (p = 0.07). Successful eradication rates for Helicobacter pylori were 85.4%, 86.7%, and 68.6% in patients with the MDR1 3435 C/C, C/T, and T/T, respectively (p = 0.02). Multiple logistic regression analysis found that MDR1 C3435T genetic polymorphisms of patients were significant independent risk factors for treatment failure, and CYP2C19 genotype did not affect Helicobacter pylori eradication. Conclusions The Helicobacter pylori eradication rates by regimens based on antibiotic susceptibility and esomeprazole were not significantly different between the CYP2C19 phenotypes. The MDR1 C3435T polymorphism is one of the factors impacting Helicobacter pylori eradication results in children.